Comparative analysis of sperm DNA fragmentation index with sperm chromatin dispersion in varied infertility types: a retrospective study - Khandhedia, Parth; Pandey, Shubhra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Infertility is a major modern concern amongst couples due to the change in their lifestyle and being carrier-oriented leading to late marriage/s. Out of all the couples suffering from infertility, approximately 30-40% cases are contributed to the male factor. As the age advances, the reduced sperm count magnifies the problem. However, in addition to that, the qualitative change along with quantity is of much more importance. Aims and objectives were to find the prevalence of sperm DNA fragmentation with sperm chromatin dispersion (SCD) test and its comparison with types of infertility Methods: The present study was retrospective that collected data from the semen sample given for routine check-up during the period of August 2022 to August 2023. A total of 138 semen analysis and sperm DNA Fragmentation Index (DFI) were carried out during this period. All 138 couples were further divided into 2 groups- 62 couples having oligozoospermia as cases and 76 couples with normozoospermia as controls and the data was compared. Results: Among 138 subjects, (62 cases and 76 control) a significant difference in the age was found. Smoking as a risk factor was found to be statistically significant. While the sperm count was not significantly different in cases and controls, a statistically significant difference was found in DFI (p=0.001) in both the groups. The highest value for DFI was 12.78 % in controls and 24.98% in cases. DFI and sperm count showed negative correlation both in DFI and sperm count with a Karl Pearson’s correlation coefficient being 0.213 (p value <0.01) and 0.754 (p value <0.005), respectively. A significant difference was observed in the median value of sperm DFI. When DFI was compared to semen analysis, it yielded 87% sensitivity and 83% specificity. Surprisingly, 13 controls out of 76 i.e. around 17.1% had poor DFI inspite of normal semen analysis parameters. Conclusions: On comparing, significant difference was observed in the median value of sperm DFI. SCD method is simple, easiest and standard tool to assess DFI.